Influence of the Lignin Extraction Methods on the Content of Tricin in Grass Lignins - Xie, Minting; Chen, Zhendong; Xia, Yue; Lin, Minsheng; Li, Jiaqi; Lan, Wu; Zhang, Liming; Yue, Fengxia (Frontiers in Energy Research, 2021)
Tricin as a monomer of grass lignin with unique biological properties is beneficial to human health with the potential for various applications. The abundant grass lignin could be an alternative source for tricin if an effective separation method is available. In this study, we used different lignin preparations, including alkali lignin (AL), mild acidolysis lignin (MAL), cellulase enzymatic lignin (CEL), γ-valerolactone lignin (GVL), and organosolv lignin (OL), to investigate the effect of different fractionation methods on the tricin content of the wheat straw lignin. The tricin signal of different lignins can be clearly identified by 2D heteronuclear singular quantum correlation (HSQC) spectra. GVL showed the highest tricin level among these lignin samples as the tricin content of GVL was accounted to be 8.6% by integrals. The tricin content was carefully determined using thioacidolysis combined with high-performance liquid chromatography-mass spectrometric (HPLC-MS), and the quantitative results of tricin by HPLC-MS were basically consistent with that of 2D HSQC integrals. Both methods have proved that the tricin contents of lignins isolated under acid conditions were significantly higher than that of AL. In addition, the determination of the sun protection factors (SPF) of lignin-based sunscreen and antioxidant activity of lignin preparations indicated that reserving more tricin was beneficial to the UV resistance of lignin samples. Therefore, this study not only provides new insights for the extraction methods of lignin with high tricin content but also is beneficial to the future study on the application of tricin and tricin-lignin.